Salivary Biomarkers of Inflammasome Activation in Unstable Periodontitis: A Case–Control Study - Hassan, Zainab Mosa; Akram, Hadeel Mazin (European Journal of Dentistry, 2025)
The objective of this study was to investigate the complex network of inflammasome-related biomarkers (NOD-like receptor thermal protein domain associated protein 3 [NLRP3], caspase-1, interleukin [IL]-1β, IL-18, and IL-37) in unstable periodontitis by examining the salivary concentrations of these specific biomarkers and correlating them with periodontal parameters.The design of this study was an observational case–control study. A salivary sample was collected from periodontally healthy patients (n = 40) and unstable periodontitis patients (n = 40). Full-mouth clinical periodontal parameters were recorded (plaque index, bleeding on probing, periodontal pocket depth, and clinical attachment loss). Enzyme-linked immunosorbent assay analyzed NLRP3, caspase-1, IL-1β, IL-18, and IL-37 salivary levels.The normality of the data was tested using the Shapiro–Wilk test. Mean, standard deviation, and percentages were used for data description. An independent sample t-test, Mann–Whitney U test, and chi-square test were used to compare the two groups with a p-value of < 0.05. Spearman's correlation analysis was conducted to examine the relationships between variables.In saliva samples, NLRP3, caspase-1, IL-1β, and IL-18 were the highest in the periodontitis group (p < 0.005), while IL-37 was highest in the healthy group (p < 0.005). There was significant (p < 0.012) negative weak correlation (−0.395) between IL-37 and IL-1β, and significant (p < 0.003) negative moderate correlation (−0.455) between IL-37 and IL-18 in the healthy group. A significant (0.031) positive weak correlation (0.342) was found between the salivary IL-37 and NLRP3, and a significant (p < 0.001) negative moderate correlation (−0.508) was found between salivary IL-37 and IL-1β, in the periodontitis group.The NLRP3 inflammasomes and their cytokines (caspase-1, IL-1β, and IL-18) significantly promote periodontal inflammation and tissue destruction. In contrast, IL-37 acts as an anti-inflammatory cytokine, inhibiting the activity of the NLRP3 inflammasome and reducing excessive inflammation. This interplay highlights the potential of targeting NLRP3 and enhancing IL-37 as a therapeutic approach for the treatment of periodontal disease.
Keywords: periodontitis; inflammasomes; caspase; saliva; interleukin